Uniting Differences : Building Multicultural Awareness In Religiounus Schools - Puspitasari, Niken Sylvia (Journal of Civics and Moral Studies, 2023)
Schools, as educational institutions that have a key role in shaping the character and values of the younger generation, have a responsibility to promote multiculturalism. However, in educational environments with a religious background, challenges can arise in efforts to promote multiculturalism without ignoring existing religious values. This research aims to examine effective strategies and approaches in instilling multicultural values in schools with a religious background. The research method used is literature reflection to explore an in-depth understanding of the concept of multiculturalism and the challenges faced by schools with a religious background. The research results show that instilling the values of multiculturalism in schools can be done through an inclusive, dialogical and religious-based approach. The integration of a multicultural curriculum that includes cultural and religious aspects from various backgrounds is an effective way to teach tolerance, respect and better understanding of differences. In addition, intercultural education that promotes interfaith dialogue, seminars, visits to places of worship, and cultural exchange programs can be a means of strengthening multicultural awareness in schools with religious backgrounds. This research also emphasizes the important role of teachers in guiding students in understanding and appreciating multiculturalism, while still recognizing the religious values they adhere to. Schools with a religious background need to create an environment that supports interfaith dialogue and encourages tolerance through inclusive educational policies and practices.